Differential immunomodulatory effects of Lactobacillus rhamnosus DR20, Lactobacillus fermentum CECT 5716 and Bifidobacterium animalis subsp. lactis on monocyte-derived dendritic cells. (April 2016) - Martínez-Abad, Beatriz; Garrote, José A.; Bernardo, David; Montalvillo, Enrique; Escudero-Hernández, Celia; Vázquez, Enrique; Rueda, Ricardo; Arranz, Eduardo
Highlights: We studied six probiotics commonly used in functional foods, and with a known effect on the maturation of human MoDCs. L. rhamnosus induced the maturation on MoDCs, which primed the differentiation of Th1 cells. L. fermentum induced a specific response on MAPK, NF-κB, AP-1 and STAT3 related genes. B. lactis had no effect on the maturation state of MoDCs and decreases the mRNA expression levels of CXCL10 . Abstract: Probiotic bacteria are widely used in functional foods or as dietary supplements. However, the signalling pathways by which they promote beneficial effects on the immune system are not fully understood. The effects of six different probiotics on monocyte-derived dendritic cells (MoDCs) were examined in this study. We found that Lactobacillus rhamnosus triggered full maturation of MoDCs, whereas L. fermentum induced a state of semi-maturation, and Bifidobacterium lactis strains barely modified MoDC basal state. Analysis of expression of genes associated with Toll-like receptor signalling revealed that B. lactis strains induced a weak pro-inflammatory response, and L. fermentum did not affect gene expression of downstream pathways, whereas it increased the expression of cytokines related with STAT3 pathway. Further insight into the pathways triggered by probiotics would facilitate a more appropriate use of probiotics to restore homeostasis in different immune disorders, like inflammatory bowel disease or allergies.